Pengembangan Human Resource Information System (HRIS) Berdasarkan Analisa Usability dengan Metode Usefullness, Satisfaction, Ease to Use (USE) Questionaire dan Cognitive Walkthrough. - Doni Prastyo; Sihab udin; Muhammad Yusuf Bakhtiar (Komunitas Dosen Indonesia, 2019)
HRIS application is an application that is needed to manage human resources well and integrated the system. Usability in a system is very necessary in the development of a system so that it can affect the use of the application. The author tests the usability user interface on HRIS products using the cognitive walkthrough evaluation method, which works through a series of task scenarios and asks a number of questions from the user's perspective, and the method of usefulness, satisfaction, ease of use (USE) Questionnaire to assess how much usability is done by the user. The cognitive walkthrough testing is done by using the application that has been made by the author, after that the author makes improvements to the system according to the results of the test. Then after being repaired, the system was tested again with the same application, then the results were assessed using the USE Questionnaire and compared with previous results. The result is that the system has increased from previously by 3.67 from a scale of 1-5 to 4.04, up by 0.34.